Evaluation of a climbing drum laminate peel test to determine the interlaminar mode I fracture toughness of thin CFRP laminates—Comparison with the standard mode I DCB test and a mandrel laminate peel test proposed by ESIS TC4 - Michel, Silvain; Hauf, Fabian; Brunner, Andreas J. (Frontiers in Materials, 2023)
The standard Mode I fracture toughness test using Double Cantilever Beam (DCB) specimens for the determination of quasi-static delamination initiation and propagation resistance, respectively is not applicable to thin fiber-reinforced laminates because of their comparatively low stiffness resulting in large deformation. Therefore, a procedure adapted from a mandrel peel test for adhesive toughness of polymer-metal laminates has been proposed for determination of fracture toughness. Another alternative has recently be proposed, analyzing the data from a climbing drum test according to ASTM D 1781 applying fracture mechanics. The present work explores further this second alternative by testing a miniaturization of the climbing-drum peel test for its applicability, robustness and sensitivity. The strain energy release rate (Gc) necessary for propagating a delamination in thin unidirectional carbon fiber laminates made with an epoxy or a polyaryletherketone matrix have been determined with three different sizes of the climbing drum, and three widths of the specimen. With specimens made from the same materials the mandrel peel tests have been performed as well. The results from both peel tests are also compared with those obtained from standard Mode I DCB tests. The Gc values gained with the three test methods agree within less than 20%, but some differences turned out to be statistically significant. The main advantage of the climbing drum peel test compared to the other two test methods is that its shows scatter of around 10%, which is less compared to the scatter of the mandrel peel test (13%) or Mode I DCB test (17%). In addition, sensitivity of the climbing-drum peel test especially for variation in material processing looks promising, which would allow using this test as a quality check method in an industrial production line. Comparison of methods and various effects of other variables, such a specimen's dimensions and layup are also presented and discussed.